1997
DOI: 10.1597/1545-1569_1997_034_0199_codcfp_2.3.co_2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2-D Calculations from Periapical and Occlusal Radiographs versus 3-D Calculations from CAT Scans in Determining Bone Support for Cleft-Adjacent Teeth following Early Alveolar Bone Grafts

Abstract: Objective This investigation was conducted to determine the agreement between three-dimensional (3-D) calculations from CAT scans and two-dimensional (2-D) calculations from standard dental radiographs in evaluating bone support for cleft-adjacent teeth after primary bone grafting. Design This retrospective study utilized CAT scans and dental radiographs taken of the alveolar cleft in patients an average of 11 years after primary bone grafting. Setting The subjects were patients treated by the Cleft Palate Tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
6

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 14 publications
1
41
0
6
Order By: Relevance
“…This study had a mean follow-up of 11 years and these numbers compared favorably with those for patients who had received secondary grafts at the Lancaster Clinic, where the mean follow-up was 3 years; the ridge heights reported in this group were 80% and 87%, respectively. 14 When cephalometric radiographs of the authors' patients were examined by others, no growth constraints were found, 15 and when compared with 13 other centers our group, with primary alveolar bone grafts, had the least amount of mandibular protrusion. 16 The maxillomandibular relationship of the primary grafted patients and facial growth have been shown to be similar to those of nongrafted patients 17 and secondary grafted patients.…”
Section: Long-term Assessment Of Early Alveolar Bone Graftingmentioning
confidence: 66%
“…This study had a mean follow-up of 11 years and these numbers compared favorably with those for patients who had received secondary grafts at the Lancaster Clinic, where the mean follow-up was 3 years; the ridge heights reported in this group were 80% and 87%, respectively. 14 When cephalometric radiographs of the authors' patients were examined by others, no growth constraints were found, 15 and when compared with 13 other centers our group, with primary alveolar bone grafts, had the least amount of mandibular protrusion. 16 The maxillomandibular relationship of the primary grafted patients and facial growth have been shown to be similar to those of nongrafted patients 17 and secondary grafted patients.…”
Section: Long-term Assessment Of Early Alveolar Bone Graftingmentioning
confidence: 66%
“…8,9 Accurate noninvasive determination of defect resolution is a challenging task, for which advanced imaging modalities are typically used. [10][11][12][13][14] This study served to demonstrate that TACT could be used for this purpose with relative ease.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used to quantify the average volume of the graft, location of the bone loss, and periodontal bone support of the cleft-adjacent teeth. CBCT-derived volumetric assessment of alveolar grafts has been reported as a reliable method [24,29,37,39,40] (Figure 2). The success rate of an alveolar graft has been found to be significantly lower with volumetric evaluation than that with conventional radiographic imaging [39,41,42].…”
Section: Advantages Of Cbct In Diagnosing and Treatment Planning Of Pmentioning
confidence: 99%